Connectionism: Alternatif dalam Memahami Dinamika Pengetahuan Lokal dalam Globalisasi - Ezra M. Choesin (Antropologi Indonesia, 2002)
The fate of indigenous knowledge systems has become the concern of many in an era of globalization. These knowledge systems are said to be under the threat of extinction, to be replaced by 'Western', 'scientific', or 'global' knowledge. The author contends that these concerns are more rooted in an overly essentialist attitude that pits the 'local' against the 'global'. He argues that the dynamics of knowledge systems must be better understood using a model of knowledge best suited for this purpose. He further argues that the most promising model is the one based on connectionism and developed by cognitive anthropologists. Drawing examples from the experience of farmers in Lampung, he shows how individuals combine stimuli from various sources to form schemas, thus showing the irrelevance of making hard distinctions between the 'local' and the 'global'.